2018
DOI: 10.1073/pnas.1721381115
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus-specific expression in the multinuclear mushroom-forming fungus Agaricus bisporus reveals different nuclear regulatory programs

Abstract: SignificanceFungi are a broad class of organisms that play crucial roles in a wide variety of natural and industrial processes. Some are also harmful, destroying crops or infecting immunocompromised patients. Many fungi, at some point during their life cycle, contain two different nuclei, each with different genetic content. We examine the regulation of genes from these nuclei in a mushroom-forming fungus. We find that these nuclei contribute differently to the regulation of the fungal cells, and may therefore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 38 publications
3
72
0
Order By: Relevance
“…Compared with traditional metabolic engineering strategies, genome engineering allows rapid tracking and discovery of novel determinants (Xiao and Zhao, 2014;Si et al, 2017), editing of key determinant with single-nucleotide precision (Garst et al, 2017;Bao et al, 2018), or simultaneous manipulating multiple pathways (Barbieri et al, 2017;Liang et al, 2017). Apart from the unicellular model organisms (e.g., Saccharomyces cerevisiae), many filamentous fungi, particularly the mushroom-forming fungi, contain two different nuclei with different genetic contents (Gehrmann et al, 2018). In addition to the heterogeneity, many important medicinal mushrooms also exhibit low efficiency on gene transformation and homologous recombination (HR), which pose a great challenge to establish gene editing tools for genome engineering (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional metabolic engineering strategies, genome engineering allows rapid tracking and discovery of novel determinants (Xiao and Zhao, 2014;Si et al, 2017), editing of key determinant with single-nucleotide precision (Garst et al, 2017;Bao et al, 2018), or simultaneous manipulating multiple pathways (Barbieri et al, 2017;Liang et al, 2017). Apart from the unicellular model organisms (e.g., Saccharomyces cerevisiae), many filamentous fungi, particularly the mushroom-forming fungi, contain two different nuclei with different genetic contents (Gehrmann et al, 2018). In addition to the heterogeneity, many important medicinal mushrooms also exhibit low efficiency on gene transformation and homologous recombination (HR), which pose a great challenge to establish gene editing tools for genome engineering (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although mature fruiting bodies of different species differ greatly in morphology, the genes regulating their development are highly conserved [11][12][13][14][15][16][17][18]. Previous studies have reported some genes involved in the fruiting body development in some species in Basidiomycete [11,[19][20][21][22][23]. Research on Pleurotus ostreatus fruiting body development, especially on stipe elongation, is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi form diverse relationships with viruses, algae, plants, animals, insects, and bacteria, and are critical to human health [15][16][17][18][19][20][21]. Filamentous fungi, in particular, are distinguished by their multinucleate cells, known as hyphae, chitinous-composite cell walls, vast repertoire of degradative enzymes and secondary metabolites, and interconnected networks of cells, known as mycelium, that form through a combination of apical growth, hyphal branching, and regulated self-fusion [22][23][24][25][26][27][28][29][30][31]. Growing mycelium penetrate and degrade the substrate upon which the organism lives and uptake and shuttle nutrients throughout complex hyphal networks [23].…”
mentioning
confidence: 99%